Developing Students’ Reading Comprehension through Think-Pair-Share Strategy - Agussatriana, Agussatriana (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The objective of the research was to find out whether or not Think-Pair-Share Strategy develops the students’ reading comprehension. The researcher applied quasi-experimental with the form of pre-test and post-test control group design and took the second year students of senior high school as the population. The researcher employed cluster random sampling consists of 60 students. The data were collected through pre-test and post-test in form of reading test. To find out whether or not Think-Pair-Share strategy develops the students’ reading comprehension, the researcher used t-test analysis. The result of the data analysis showed that the value of t-counted (5.747) was greater than the value of the t-table (2.002) at the level of significance (a = 0.05) and the degree of freedom df = 58 which meant that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Based on the result of data analysis, the mean score of students’ post-test (84.44) was greater than the mean score of students’ pre-test (63.11). Based on the finding and discussion, the researcher concludes that Think-Pair-Share strategy is effective and gives positive effect to the students’ reading comprehension achievement.